2019
DOI: 10.3390/su11205748
|View full text |Cite
|
Sign up to set email alerts
|

The Interdependences between Sustainability and Their Lifestyle That Pre-Service Teachers Establish When Addressing Socio-Ecological Problems

Abstract: In the training of pre-service teachers, promoting changes in everyday activities to favour environmental conservation is still a challenge. This paper discusses the main difficulties of pre-service teachers in the process of building relationships between sustainability and their lifestyle. For this purpose, a problem-based learning programme was designed, consisting of three socio-ecological problems. In each of them, we analysed three components which define these interdependences: pressures, importance and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 59 publications
(110 reference statements)
2
11
0
Order By: Relevance
“…In this regard, our results are in line with those reported by references [10,98], in which, despite the progression of the knowledge that students showed about the causes and consequences of different socio-ecological problems, there still exist important barriers to achieve the generation of commitments and changes towards individual pro-environmental behaviors; in other words, it does not directly mean that this progression could be translated into real individual actions. Reference [10] also concluded that students show some difficulties to recognize the social and economic dimensions of socio-ecological problems. Therefore, future uses of the sequence described here should emphasize the socio-economic importance of coral reefs, as well as the impacts of our individual and local actions on global and, sometimes, distant socio-ecological systems, since intentions of taking pro-environmental action may be activated "when students believe that things they value are in danger" [99] (p. 4).…”
Section: Discussion and Educative Implicationssupporting
confidence: 91%
See 4 more Smart Citations
“…In this regard, our results are in line with those reported by references [10,98], in which, despite the progression of the knowledge that students showed about the causes and consequences of different socio-ecological problems, there still exist important barriers to achieve the generation of commitments and changes towards individual pro-environmental behaviors; in other words, it does not directly mean that this progression could be translated into real individual actions. Reference [10] also concluded that students show some difficulties to recognize the social and economic dimensions of socio-ecological problems. Therefore, future uses of the sequence described here should emphasize the socio-economic importance of coral reefs, as well as the impacts of our individual and local actions on global and, sometimes, distant socio-ecological systems, since intentions of taking pro-environmental action may be activated "when students believe that things they value are in danger" [99] (p. 4).…”
Section: Discussion and Educative Implicationssupporting
confidence: 91%
“…Nonetheless, according to numerous authors, this improvement on their knowledge of natural phenomena and humans' impact on the environment is not enough to increase their individual responsibility and to act sustainably [96,97]. In this regard, our results are in line with those reported by references [10,98], in which, despite the progression of the knowledge that students showed about the causes and consequences of different socio-ecological problems, there still exist important barriers to achieve the generation of commitments and changes towards individual pro-environmental behaviors; in other words, it does not directly mean that this progression could be translated into real individual actions. Reference [10] also concluded that students show some difficulties to recognize the social and economic dimensions of socio-ecological problems.…”
Section: Discussion and Educative Implicationssupporting
confidence: 84%
See 3 more Smart Citations